Learning the TEI in a Digital Environment - Stella Dee (OpenEdition, 2014)
This article provides a brief overview of currently-available digital resources for learning to understand and use the TEI Guidelines. It reflects on and analyzes these resources and their audience through the results of a survey intended to inform future support from the TEI Consortium for novice users. Increasing numbers of students look online for self-directed and task-based tutorials, and increasing numbers of scholars in the humanities recognize the TEI Guidelines as a standard tool for publication and analysis. In this context, the author designed the survey presented in this paper to solicit qualitative feedback from both experienced and aspiring practitioners in the field concerning their skills, needs, and goals, pedagogical as well as technical. The article suggests revising and expanding TEI community resources, proposing possibilities for their new form and functionality.